Relevansi Nilai-Nilai Multikultural Dalam Buku Pendidikan Agama Islam dan Budi Pekerti dengan Dimensi Projek Penguatan Profil Pelajar Pancasila - Nurul Hidayati; Achmad Yusuf; Moch. Nasir; Askhabul Kirom (Academicus: Journal of Teaching and Learning, 2023)
Multicultural values ​​are very important for students to understand because this will build a noble personality, love of the homeland, love of culture. This research will analyze the suitability of multicultural values ​​contained in PAI student textbooks for class VII SMP with the Project Dimensions of Strengthening the Pancasila Student Profile. This research uses a qualitative approach with a library research type. Data collection was carried out by reviewing documents, namely textbooks for students of Islamic Religious Education and Characteristics at Grade VII Middle School. Data analysis techniques include content analysis and critical analysis. Checking the validity of the findings was carried out using triangulation techniques. The value of tolerance contains 4 dimensions P5, these dimensions are the dimensions of faith and devotion to God Almighty, independence, mutual cooperation and global diversity. The democratic values ​​contain 3 P5 dimensions, namely the dimensions of independence, mutual cooperation and global diversity. The value of humanism contains 4 dimensions, namely the dimensions of independence, mutual cooperation, global diversity and creativity. Meanwhile, the value of equality contains 4 P5 dimensions, namely the dimensions of faith and devotion to God Almighty, independence, mutual cooperation and global diversity.